ASSESSMENT OF ICE HOCKEY TEAM "RIGA 2000"OF FORWARDS, DEFENSIVES AND GOALKEEPER PLAYERS OF FUNCTIONAL FITNESS PREPAREDNESS AND ANTHROPOMETRY PARAMEETERS AT BEGINING OF 2015./2016. SEASON - Svarinskis, Mihails; Ķīsis, Igors (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The Aim of the Study is assessment the hockey players of team "Riga 2000" overall functional fitness preparedness and anthropometric parameters indicators according to their age. In study voluntarily participated 23 ice hockey players: 12 of them were forwards – players (first group), 8 of them were defenses – players and 3 of them were – goalkeepers (second group). For physical fitness testing we used "Eurofit" method. Testing was executed in Latvian Sport medicine center beginning overall preparation period of the season 2015/2016th, end of July. Evaluating the hockey players of team "Riga 2000" of forwards players (first group), defenses players and goalkeepers (second group) overall functional fitness preparedness and average anthropometric parameters indicators according to their age after "Eurofit" criteria we can see that the most part of indicators comply with the assessment – medium and under medium level.